Chemical desulphurisation of low rank Mae Moh coal via mixtures of hydrogen peroxide and hydrochloric acid solution, a mild oxidising treatment / Azil Bahari Alias - Alias, Azil Bahari (2004)
Combustion of coals to produ ce energy has created environmental problems such as sulphur, which is converted to S0₂ and S0₃ gases and the ash product. In order to produce a "clean coal" , the pre-treatment processes of sulphur removal from coal have to be effective to remove sulphur and ash without severe affects on the coal microstructure and calorific value. In this study , a mild oxidising treatment of H₂0₂ and HCl mixtures has been identified to remove sulphur and ash from low rank Mae Moh III coal (MM3). The optimum conditions achieved were 30ml 6% (0₂ content) peroxide: 70ml O.lN HCI (reagent volume mixed ratio) with leachin g temperature and time of 50°C and 8 hours , respectively. Under thes e conditions, c.a. 53%, 88%, 100%, 37% and 72% of sulphurtotal, sulphurpyrite, sulphursulphate, sulphur organic and ash were removed with 31% of coal dissolution were achieved , respectivel y. Preliminary study of desulphurisation at elevated pressure was also carried out under the optimal conditions. The results indicated that , sulphurorganic removal of fresh and pyrite-free coals were further increased to 30 and 40%, respectively. Different protic acids mixed with perox ide (H₂S0₄ and HN0₃), coal and single-reagent treatment (unmixed reagent) were also applied under the optimal conditions. The results showed that , mixtures of H₂0₂ : HCl gave higher sulphurtotal removal. Furthermore, it was found that no synergi stic effect was contributed by single-reagent treatment on the desulphurisation of MM3. The mild oxidising treatments slightly affected the coal micro structure as revealed by Scanning Electron Microscope - Energy Dispersive X-ray. Likewise, the calorific value of the treat ed coal samples was not affected as analyzed by bomb calorim eter. A kinetic analysis on pyritic remov al reaction of MM3 was found to correlat e well with a second -order rate equation that gave activation energy of 61.4 x 10⁶J kmorl־¹.